Effect of three different irrigation solutions applied by passive ultrasonic irrigation - Carmen Llena; Leopoldo Forner; Raquel Cambralla; Adrian Lozano (Korean Academy of Conservative Dentistry, 2015)
Objectives This study evaluated the maximum depth and percentage of irrigant penetration into dentinal tubules by passive ultrasonic irrigation (PUI). Materials and Methods Thirty extracted human teeth were instrumented and divided into three groups. According to final irrigation regimen, 5.25% sodium hypochlorite (Group A, NaOCl), 2% chlorhexidine (Group B, CHX) and saline solution (Group C, control group) were applied with Irrisafe 20 tips (Acteon) and PUI. Irrigant was mixed with 0.1% rhodamine B. Sections at 2 mm, 5 mm, and 8 mm from the apex were examined with confocal laser scanning microscopy (CLSM). The percentage and maximum depth of irrigant penetration were measured. Kruskal-Wallis test and Mann-Whitney test were performed for overall comparison between groups at each level and for pairwise comparison, respectively. Within a group, Wilcoxon test was performed among different levels. p values less than 0.05 were considered significant. Results In all groups, highest penetration depth and percentage of penetration were observed at the 8 mm level. At 2 mm level, Groups A and B had significantly greater depths and percentages in penetration than Group C (p < 0.05), but there were no significant differences between Groups A and B. At 5 mm level, penetration depths and percentage of penetration was not significantly different among the groups. Conclusions NaOCl and CHX applied by PUI showed similar depth and percentage of penetration at all evaluated levels.